Excitation functions of alpha particles induced nuclear reactions on natural titanium in the energy range of 10.4–50.2 MeV - Usman, Ahmed Rufai; Khandaker, Mayeen Uddin; Haba, Hiromitsu; Otuka, Naohiko; Murakami, Masashi (Elsevier, 2017)
We studied the excitation functions of residual radionuclide productions from α particles bombardment on natural titanium in the energy range of 10.4–50.2 MeV. A well-established stacked-foil activation technique combined with HPGe γ-ray spectrometry was used to measure the excitation functions for the 51,49,48Cr, 48V, 43K, and 43,44m,44g,46g+m,47,48Sc radionuclides. The thick target yields for all assessed radionuclides were also calculated. The obtained experimental data were compared with the earlier experimental ones and also with the evaluated data in the TENDL-2015 library. A reasonable agreement was found between this work and some of the previous ones, while a partial agreement was found with the evaluated data. The present results would further enrich the experimental database and facilitate the understanding of existing discrepancies among the previous measurements. The results would also help to enhance the prediction capability of the nuclear reaction model codes.